THE WORLD TENDENCIES OF INNOVATIVE VENCHUR SYSTEM DEVELOPMENT - Akramovich, A tamuradov Sherzod (International Journal of Psychosocial Rehabilitation, 2020)
In the conditions of economic modernization, high-tech industries and additional financial resources are needed to develop innovative projects. This article analyzes both traditional and modern sources of risk investing, as well as mechanisms and models for Venchur Innovation Design in different countries. Innovative venture design is a new and fast-paced sector of the economy that combines the mechanisms for introducing and commercializing innovation. In this work, the mechanisms and models of Venture Innovation Design in different countries, mechanisms for implementing venture capital and innovation are discussed in detail. The purpose of the study is to evaluate the possibilities of alternative means of venture financing of innovative projects. We believe that the introduction of the mechanisms and experience of the developed countries of innovative technologies of Venture innovation in the economy of our country will be positive.